Professional Challenges to Women as Educators and as Mothers - Galili, Iris (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
This article explores the dynamic between the professional roles of women working in early childhood education and their maternal skills and identities. This dynamic reveals a blurring of the boundaries between motherhood and career, which have similar requirements to provide protection, care, and concern. This study sheds light on the perspectives of mothers working in early childhood education regarding their personal and professional lives. It highlights not only the conflicts raised and prices paid by the women and their children but also the extent to which female educators bring their profession home with them, including their theoretical and practical knowledge. These women continue to act as educators at home, but the demands on them are multiplied in the private sphere, where they are also mothers. Moreover, the demands they place on their children can also be influenced by the private domain, making this relationship complex and conflictual. Oftentimes, the private life and children of a female educator are seen as significant aspects of the “business card” she is expected to present to the world in order to gain respect in her professional life. Specifically, this article explores how female educators who are also mothers experience the relationships existing between the professional and personal realms.